2023
DOI: 10.56553/popets-2023-0017
|View full text |Cite
|
Sign up to set email alerts
|

SoK: Secure E-Voting with Everlasting Privacy

Abstract: Vote privacy is a fundamental right, which needs to be protected not only during an election, or for a limited time afterwards, but for the foreseeable future. Numerous electronic voting (e-voting) protocols have been proposed to address this challenge, striving for everlasting privacy. This property guarantees that even computationally unbounded adversaries cannot break privacy of past elections. The broad interest in secure e-voting with everlasting privacy has spawned a large variety of protocols over the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Beyond the individual pros and cons of the various proposals, a recent systematic review has identified a global problem [28]: there is no secure and efficient Internet voting system that can simultaneously mitigate the effects of malicious influence and keep votes secret in the long term. In fact, in all state-of-the-art systems that limit coercion or vote buying, such as BeleniosRF, JCJ/Civitas or VoteAgain, votes are encrypted using the tellers' public key and the resulting ciphertexts are then posted on a bulletin board for verification purposes.…”
Section: State Of Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond the individual pros and cons of the various proposals, a recent systematic review has identified a global problem [28]: there is no secure and efficient Internet voting system that can simultaneously mitigate the effects of malicious influence and keep votes secret in the long term. In fact, in all state-of-the-art systems that limit coercion or vote buying, such as BeleniosRF, JCJ/Civitas or VoteAgain, votes are encrypted using the tellers' public key and the resulting ciphertexts are then posted on a bulletin board for verification purposes.…”
Section: State Of Researchmentioning
confidence: 99%
“…This state of research is unsatisfactory because many elections require confidentiality to be guaranteed not just for some time, but for several decades because voters may have to fear negative consequences even if their individual choices are revealed, say, 10 or 20 years after the election. Instead, electronic voting systems should provide everlasting privacy [28], i.e. privacy without relying on any hardness assumption.…”
Section: State Of Researchmentioning
confidence: 99%
See 2 more Smart Citations